The SIK1/CRTC2/CREB1 and TWIST1/PI3K/Akt/GSK3β signaling pathways mediated by microRNA-25-3p are altered in the schizophrenic rat brain - Pan, Bo; Zhu, Xiaoli; Han, Bing; Weng, Jianjun; Wang, Yuting; Liu, Yanqing (Frontiers in Cellular Neuroscience, 2023)
Schizophrenia is a group of severe mental disorders. MiR-25-3p was shown to be involved in various neuropsychiatric diseases and can regulate SIK1 and TWIST1. The CRTC2/CREB1 and PI3K/Akt/GSK3β signalling pathways are downstream pathways of SIK1 and TWIST1, respectively. This study investigated whether miR-25-3p-mediated SIK1/CRTC2/CREB1 and TWIST1/PI3K/Akt/GSK3β signalling pathways are present in an animal model relevant to schizophrenia. A schizophrenic rat model was established by using sub-chronic MK-801 administration. An RNA-seq test was performed to examine the differentially expressed genes (DEGs) in the rat prefrontal cortex (PFC). The mRNA levels of miR-25-3p, SIK1, and TWIST in the PFC and caudate putamen (CPu) were assessed by qRT-PCR. Phosphorylation of the SIK1/CRTC2/CREB1 and TWIST1/PI3K/Akt/GSK3β pathways in the two brain regions was examined by Western blots. The RNA-seq data revealed down-regulated miR-25-3p expression and up-regulated SIK1 and TWIST1 mRNA expression induced by MK-801. Additionally, SIK1 and TWIST1 were shown to be possible downstream responders of miR-25-3p in previous studies. qRT-PCR confirmed the changes of miR-25-3p, SIK1, and TWIST1 induced by MK-801 in both brain regions, which however was reversed by risperidone. Furthermore, the phosphorylation of the SIK1/CRTC2/CREB1 pathway was repressed by MK-801, whereas the phosphorylation of the TWIST1/PI3K/Akt/GSK3β pathway was increased by MK-801 in either of the two brain regions. Moreover, the altered phosphorylation of these two signalling pathways induced by MK-801 can be restored by risperidone. In conclusion, this study suggests that altered SIK1/CRTC2/CREB1 and TWIST1/PI3K/Akt/GSK3β signalling pathways mediated by miR-25-3p is very likely to be associated with schizophrenia, revealing potential targets for the treatment and clinical diagnosis of schizophrenia.